Proses morfologi derivasional dan infleksional dalam perkembangan struktur kata - maulidia, yurin syafa (Maliki Interdisciplinary Journal, 2026)
This study examines in depth the processes of derivational and inflectional morphology in Indonesian. Derivational morphology is the process of producing new lexemes through the addition of affixes that can change word classes and basic meanings. Meanwhile, inflectional morphology functions to change word forms without creating new meanings, but regulates the role of words in grammatical structures. This article discusses the differences in concepts, characteristics, and examples of their application in everyday life. Derivational morphology focuses more on developing understanding, while inflection plays a role in maintaining grammatical regularity. These two processes complement each other in the Indonesian morphological system, particularly in the formation of meaning, sentence structure, and language productivity. This study uses a descriptive-qualitative approach with linguistic analysis methods on linguistic data obtained from written texts and spoken Indonesian. The data were analyzed by identifying forms of affixation, reduplication, and morphemic changes that represent derivational and inflectional processes. The results of the study indicate that derivational processes tend to be productive in the formation of new vocabulary, especially in the realms of education, media, and everyday communication, while inflectional processes play an important role in maintaining the clarity of syntactic functions and grammatical relationships between elements in sentences. Thus, understanding these two morphological processes is not only important in theoretical studies, but also has practical implications in Indonesian language learning, particularly in improving language competence and awareness of language structure in speakers.